Giant juvenile fibroadenoma of breast in adolescent girls - Saif AlGhamdi; Abdullah Ghouth Ali; Safi Nassan Ali; Khalid Rasheed; Yasmin Yousef (Elsevier, 2018)
Giant juvenile fibroadenomas are rare variants of fibroadenoma, usually occurring in girls between the ages of 10 and 18 years. They are characterized by massive and rapid enlargement of a rubbery, mobile, and non-tender mass. The etiology is not well understood and believed to be an increased sensitivity to normal estrogen level. We report two cases of giant juvenile fibroadenoma in a 12 and 14 years old girls that were managed by surgical excision with conservation of normal breast tissue, nipple, and areola. The cases are followed by a literature review. Keywords: Giant fibroadenoma, Juvenile fibroadenoma, Benign breast lump